2017
DOI: 10.1177/1352458517717088
|View full text |Cite
|
Sign up to set email alerts
|

Optimal response to dimethyl fumarate associates in MS with a shift from an inflammatory to a tolerogenic blood cell profile

Abstract: A pro-tolerogenic shift in the blood leukocyte profile associates with an optimal response to DMF in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 29 publications
11
53
3
Order By: Relevance
“…In line with other publications, DMF therapy was associated with reduced CD8 + T cell and B cell counts among total PBMC (Fig. K and L) …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In line with other publications, DMF therapy was associated with reduced CD8 + T cell and B cell counts among total PBMC (Fig. K and L) …”
Section: Resultssupporting
confidence: 93%
“…Furthermore, mDC from DMF‐treated MS patients exhibit a rather immature phenotype with reduced expression of costimulatory molecules and impaired T‐cell activation capacity . Lower numbers of circulating mDC, CD8 + cytotoxic T cells and B lymphocytes but enhanced CD56 bright NK cell frequencies in the blood of DMF‐treated MS patients further support the concept of an anti‐inflammatory shift in the peripheral immune cell compartment probably mediated by NRF2 activation . Close associations between a reduction in B lymphocytes, respectively, an increase in regulatory CD56 bright NK cells and a good response to treatment were previously described for other immunomodulatory drugs .…”
Section: Discussionsupporting
confidence: 72%
“…Although not addressed in this work, it would be interesting to analyze the expression of CXCR3 and CCR6 in the Treg population to know whether this reduction is related to a decrease of pro‐inflammatory Th1 and/or Th17 Treg . Regarding discrepancies with other studies reporting a reduction on Th1 and Th17 cells and no alteration or even expansion of Treg, they might be caused by the use in those studies of isolated, cryopreserved, and stimulated PBMC (since it has been reported that these procedures can modify the expression of chemokine receptors) . We consider that the direct analysis of whole blood leukocytes subpopulations can reflect better the effects caused by DMF treatment, avoiding variability caused by cell manipulation.…”
Section: Discussionmentioning
confidence: 92%
“…Studies focused on the mechanism of action of DMF demonstrated that the treatment induces lymphopenia, selectively depleting memory T and B cells and promoting a shift toward a tolerogenic immune profile . Specifically, Medina and colleagues reported that DMF induces a change in the ratio between regulatory CD56 bright NK cells and effector TNF‐α‐producing CD8 + T cells, which is required for the efficacy of the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation